Interaction between Antiphospholipid Antibodies and Protein C Anticoagulant Pathway: A Narrative Review - Pengo, Vittorio (Seminars in Thrombosis and Hemostasis, 2022)
Thrombotic antiphospholipid syndrome (APS) is a condition in which thrombosis in venous, arterial, and/or small vessels is ascribed to the presence of antiphospholipid antibodies (aPL). Among the various proposed pathogenic theories to explain thrombotic APS, those involving the interaction between aPL and the protein C system have gained much consensus. Indeed, robust data show an acquired activated protein C resistance (APC-R) in these patients. The role of aPL in this impairment is clear, but the mechanism of action is uncertain, as the type of aPL and to what extent aPL are involved remains a gray area. Lupus anticoagulant (LA) is often associated with APC-R, but antibodies generating LA comprise those directed to β2-glycoprotein I and antiphosphatidylserine/prothrombin. Moreover, the induction of APC-R by aPL requires the presence of phospholipids and is suppressed by the presence of an excess of phospholipids. How phospholipids exposed on the cell membranes work in the system in vivo is unknown. Interestingly, acquired APC-R due to aPL might explain the clinical phenotypes of thrombotic APS. Indeed, the literature reports cases of both venous and arterial thromboembolism as well as skin necrosis, the latter observed in the severe form of protein C deficiency and in catastrophic APS.
Keywords: protein C; resistance; phospholipid; syndrome; antibodies; thrombosis; lupus anticoagulant